PENGARUH E-COMMERCE, SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - I Kadek Dodik Aditya; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
This study aims to determine the effect of e-commerce, the use of accounting information systems and internal control on the company's financial performance. This research was conducted in Denpasar City with UMKM as research subjects . The population in this study were all UMKM in Denpasar City with a total of 32,226. The sampling method used in this study was purposive sampling with the sample size determined by the Slovin formula. Samples used is 102 samples. Collecting data using a questionnaire with data analysis and multiple linear regression analysis. Results of this study indicate that ecommerce has a positive effect on the company's financial performance. Accounting information systems has a positive effect on the company's financial performance. Internal control has a positive effect on the company's financial performance. For UMKM owners in Denpasar City, the results of this study can be used as a reference and theoretical basis in improving the company's financial performance. This can be done by optimizing the use of e-commerce, so that consumers will feel more secure in conducting transactions. Optimizing the use of accounting information systems within the company in order to know the increase or decrease in capital experienced by the company. Optimizing existing internal controls in the company by conducting regular and periodic financial evaluations so as to reduce the possibility of financial fraud in the company